Rationale and protocol of the LEAD 2.0 study: a randomized controlled trial assessing the feasibility of a virtually delivered 6-month exercise and nutrition intervention in older adults with subjective cognitive decline (SCD) - Bobby Neudorf; Noah Koblinsky; Krista Power; Malcom Binns; Alexandra J. Fiocco; Shlomit Rotenberg; Susan Marzolini; Paul Oh; Jane Thornton; Fatim Ajwani; Kylie Sullivan; Stéphanie Chevalier; et al. (Pilot and Feasibility Studies)
Abstract Background With growing prevalence of dementia worldwide, dementia risk reduction is a key interest of the World Health Organization’s Global Dementia Action Plan. Subjective cognitive decline (SCD) is a prominent predictor of future dementia diagnosis. Therefore, people with SCD are an important group for dementia prevention intervention. Exercise and healthy diet are associated with a 30–60% decrease in dementia risk in longitudinal studies. Technological advances yield the potential of trials that deliver lifestyle interventions virtually, reaching people in a wide geographical spread. However, the feasibility of large-scale virtual trials still needs to be established. Objective This trial aims to examine the feasibility of a factorial randomized controlled trial exploring a 6-month virtual, exercise and healthy diet intervention. Secondary objectives will examine whether feasibility outcomes vary by gender or technology access. Methods We will recruit 140 older adults (65 + years) with SCD, who will receive a combination of Aerobic and Resistance Exercise (EX) or Stretching and Toning (STRETCH) and either Diet Counseling (DIET) or Brain Health Education (ED). Participants will be randomized to four weekly hours of one of four intervention arms: (1) EX and DIET; (2) EX and ED; (3) STRETCH and DIET; or (4) STRETCH and ED. EX will include moderate intensity aerobic and resistance training. DIET will instruct participants in brain healthy food choices. Assessments will be performed virtually at baseline, 6 months (post-intervention), and 12 months. Feasibility will be measured by recruitment rate, adherence, and retention. Discussion Established feasibility will set the stage for a definitive trial. Feasibility results will also inform future virtual programs/services. In the long-term, if the interventions are feasible and beneficial, this intervention model could scale up and spread quickly to reach at-risk individuals for the purpose of dementia risk reduction. Trial registration The Lifestyle, Exercise, and Diet (LEAD 2.0) study is registered with the US National Institutes of Health clinical trials registry (ClinicalTrials.gov identifier NCT06078748). This report complies with the Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) statement.